“APA NAMANYA”: KAJIAN SENYAPAN FRASA PENJEDA PADA PEMBICARAAN PUBLIK - Triyanto Triyanto (STKIP Siliwangi, 2021)
Speaking is not only about using language as a medium for delivering messages from the sender to the recipient, but also activities that involve brain work. In language activities, speakers who produce language orally are also producing language structures in their brains. This working paper aims to describe the pause phrases that often appear every time there is a public conversation. In addition, the presentation will also explain about language activities outwardly which are in line with the language process that is conceptualized in the mind, namely that every conversation sometimes stops because there are certain factors such as nervousness and other psychological conditions. The method used in this research is descriptive qualitative. The data in this study is the speaking word apa namanya in the verbal communication process produced by public speakers in conducting oral presentations in a scientific forum. Data analysis using taxonomic theory expressed by Leonard Bloomfield about linguistic behaviorism. Another theory is the outer structure and inner structure proposed by Noam Chomsky. Based on the analysis carried out, it was found that the word pause emerged from public speakers in scientific forums as a form of behavior that showed a reaction to the stimulus in the mind. These stimuli include nervousness, confusion, forgetfulness, and loss of concentration. The reaction appears with language behavior in the form of the emergence of a pause word to collect scattered focus and plan the next conversation. Based on these results, the speaking pause is used by public speakers to stay in control of the forum and to stay in the flow of the conversation.